A leaf-specific phage T7 RNA polymerase-based system for transgene expression in tobacco chloroplasts - Magee, Alan (Trinity College (Dublin, Ireland). School of Genetics and Microbiology, 2001)
This thesis describes the development of a chloroplast-localised gene expression system based on the phage T7 RNA polymerase. In order to direct T7 RNAP expression in a leaf-specific manner and to target it to the chloroplast, we constructed three chimeric genes (st8, st14 and st25) in which tobacco rbcS sequences encoding the Rubisco small subunit (SSU) transit peptide and either the first 8, 14 or 25 amino acids of mature SSU were fused in-frame with the coding sequence of T7 RNAP. Transgenic tobacco plants expressing the STB, STM and ST25 chloroplast-targeted fusion proteins in their leaves were generated using the Agrobacterium system for nuclear transformation. These transgenic plants were shown to express a chloroplastlocalised transcriptional activity which was specific for the phage T7 DNA template. All transgenic lines grew normally, the transgenes were inherited in a Mendelian fashion in the progeny, and homozygous lines expressing the STM and ST25 fusion proteins were identified. We further determined that a large proportion of all three ST fusion proteins was localised within the chloroplast. In addition we determined that the ST25 fusion protein had an in vivo half-life of at least 16 days in the dark and that the transcription of eight plastid genes in the ST25 line appeared to be unaltered by the presence of the T7 RNAP activity.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin